2018
DOI: 10.1101/400275
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Topological data analysis quantifies biological nano-structure from single molecule localization microscopy

Abstract: The study of complex molecular organisation and nanostructure by localization based microscopy is limited by the available analysis tools. We present a segmentation protocol which, through the application of persistence based clustering, is capable of probing densely packed structures which vary in scale. An increase in segmentation performance over state-of-the-art methods is demonstrated. Moreover we employ persistent homology to move beyond clustering, and quantify the topological structure within data. Thi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Since the cluster centers were set to be at least two standard deviations apart from each other, the individual clusters can be correctly identified by eye (Figure 2A) and as well with DBSCAN (Figure 2C) and ToMATo (Figure 2D). In contrast and as shown before (Pike et al, 2020), the approach based on Ripley's K-function (Figure 2B) fails to separate nearby clusters and thus commonly misidentifies cluster number and area (Figures 2E,F). As previously shown, this behavior is due to the incapability of this approach to correctly take into account the local density of the data points (Rubin-Delanchy et al, 2015;Griffié et al, 2017).…”
Section: Benchmarkingmentioning
confidence: 54%
See 3 more Smart Citations
“…Since the cluster centers were set to be at least two standard deviations apart from each other, the individual clusters can be correctly identified by eye (Figure 2A) and as well with DBSCAN (Figure 2C) and ToMATo (Figure 2D). In contrast and as shown before (Pike et al, 2020), the approach based on Ripley's K-function (Figure 2B) fails to separate nearby clusters and thus commonly misidentifies cluster number and area (Figures 2E,F). As previously shown, this behavior is due to the incapability of this approach to correctly take into account the local density of the data points (Rubin-Delanchy et al, 2015;Griffié et al, 2017).…”
Section: Benchmarkingmentioning
confidence: 54%
“…We found that typical runtimes for Ripley's K-based and DBSCAN clustering were 25.78 ± 0.86 and 28.45 ± 0.78 min, respectively (mean ± standard deviation). The ToMATo implementation from the RSMLM package (Pike et al, 2020) had a runtime of 23.87 ± 0.80 min (mean ± standard deviation, Figure 3). By parallelizing the clustering and scoring process to multiple cores, we found the computation time to decrease by 60% for Ripley's K-based, 10.41 ± 0.23 min, and DBSCAN, 11.90 ± 0.27 min (Figure 3).…”
Section: Benchmarkingmentioning
confidence: 99%
See 2 more Smart Citations
“…In life sciences, topological data analysis (TDA) has previously been applied in medical imaging [13,29], protein characterization [8,17], describing molecular architecture [24,26], and cancer genomics [3,21]. There have been several studies exploring TDA in genomics [7].…”
Section: Introductionmentioning
confidence: 99%